Strategies for Quality Culture Development of Public Basic Education Schools - Aridech, Sutheerat; Yawirach, Punchai (Ratchaphruek Journal, 2014)
The purposes of this descriptive research were to study: 1) elements of quality culture, 2) conditions and success factors in developing a quality culture, and 3)strategies for quality culture development of public basic education schools. The research methodology was divided into 5 stages; 1)to study elements of the quality culture in public basic education schools by using questionnaire with school administrators and teachers who were responsible in the educational quality assurance. The sample group was randomized by using a multi-stage sampling. Data were analyzed by using percentage, mean, standard deviation and exploratory factor analysis. Moreover, the in-depth interview was collected and analyzed by using content analysis, 2) to study conditions and success factors in developing quality culture of public basic education schools by using in-depth interview with school administrators and teachers, and conducting by using the focus group discussion. The data were then analyzed by using content analysis, 3) to formulate the strategies for developing a quality culture of public basic education schools by conducting the focus group discussion and then analyzed the data by content analysis. 4) to evaluate the appropriateness and feasibility of the strategies by using a questionnaire and the data was then analyzed via mean, standard deviation and content analysis and 5) to identify the strategies, the research results found that the quality culture in public basic education schools was categorized into 7 elements: Leadership for Quality, Teamwork, Decision Making, Systematic Operation, Customer Focus, Human Resource Development, and Quality Assessment. Condition and success factors in developing the quality culture of public basic education schools consisted of the external factors which comprised political-legal, economic, sociocultural and technological factors. These factors indirectly impacted to all elements of the quality culture. On the other hand, the internal factors which comprised strategies, structures, systems, staffs, skills, styles, shared values. Also, quality awareness and participation were consistent with each of quality culture elements in different details. The strategies for quality culture development of public basic education schools composed of 7 strategies; 1) Develop the leadership for Quality of school administrators, 2) Encourage quality team working of personnel in school, 3) Encourage decisions making based on the quality 4) Encourage the process of quality management in schools, 5) Focus on student’s qualities, 6) Encourage the development of the personnel quality in schools, and 7) Focus on outcome-based assessment. All 7 strategies were appropriate and feasible at the highest level.